EDUCATING STUDENT AT MUSEUM - Anwari, Hamdan; F, Fian Damasdino; Afif, Fuadi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Museums are buildings used as storage, maintenance, security and utilization of historical relics, art and science for permanent exhibition to the public (tourists) as a tourist attraction that provides educational values to tourists or visitors. To meet the needs of visitors in the museum, competent tour guides are needed as parties who provide information or provide education about the collections owned by the museum being visited. Therefore, the purpose of this journal is to review how tourists learn in museums through tour guides and what the role of tour guides as educators is, namely guiding tourists, providing information, introducing new things from the museum to visitors, informing visit regulations about things that can and cannot be done while in the museum and maintaining quality service. To fulfill the criteria of tour guides and maintain the quality and service to visitors, it is necessary to have continuous training for tour guides. This research uses a descriptive qualitative research method that aims to analyze and describe how visitors or tourists gain understanding or knowledge about the museum through the role of tour guides and what kind of tour guides educate visitors. Researchers use several methods library data collection methods, reading and recording, and processing research materials. In this study, researchers found that tour guides have an important role as educators to educate tourists from the beginning to the end of a visit to the museum.